INTERPRETASI PUTUSAN HAKIM MAHKAMAH AGUNG TERHADAP PERKARA KORUPSI BERBASIS HUKUM PROGRESIF - carera, famelinda (jurnal.unprimdn.ac.id, 2023)
This is the main issue in a study of what interpretation is as part of a legal discovery method based on progressive law in corruption cases. This study aims to study and explain the importance of legal interpretation regarding the formulation of legal texts (laws) that have legal certainty for a law enforcer to maintain the value of justice and the benefits of law, especially in corruption cases. The type of research study used is a normative juridical research study, namely a type of research study that uses legal research analysis methods through a statutory approach. The research results concluded that Supreme Court Judge Artidjo Alkostar, in applying the article at the cassation level, interpreted it progressively by first looking at the elements of the criminal act that the Defendant had committed. The elements of legal violations that have been fulfilled are then adjusted to the articles that have been alleged. In the adjustments made, Supreme Court Justice Artidjo Alkostar used language interpretation techniques. In addition, Supreme Court Justice Artidjo Alkostar considers the Defendant taking advantage of his public position (political corruption) to commit corruption crimes as a factor that complicates sanctions for perpetrators of corruption.